DADAP (ERYTHRINA SUMBUBRANS) AS HINDU ETHNOMEDICINE FROM LONTAR USADHA TARU PRAMANA - Ni Ketut Sinarsih; Mery Ambarnuari; I Gusti Agung Ayu Kartika (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Dadap (Erythrina sumbubrans), a plant native to Bali, has been one of the foundations of Balinese ethnomedicine and Hindu ceremonies for centuries. delves into the multifaceted role of Dadap in traditional healing practices and its cultural significance within Hinduism. The plant is characterized by its expansive green, heart-shaped leaves and vibrant red flowers, which are highly valued for their medicinal and spiritual properties. In Hindu ceremonies, Dadap is respected as